1994
DOI: 10.2118/26564-pa
|View full text |Cite
|
Sign up to set email alerts
|

Frac-and-Pack Stimulation: Application, Design, and Field Experience

Abstract: Paper first presented at the 1993 SPE Annual Technical Conference and Exhibition held in Houston, Oct. 3-6. Combined with SPE 26563 and published in the Journal of Petroleum Technology, March 1994. Summary A relatively short, highly conductive fracture created in a reservoir of moderate to high permeability will breach near-wellbore damage, reduce the drawdown and near-wellbore flow velocity and stresses, and increase the effective wellbore radius. Fracturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Because of the complicated flow regime usually occurring after hydraulically fracturing wells with deep damage, it is expected that a small positive skin factor is calculated from buildup data. 1,3 What is observed in Table 1 is consistent with previously published modeling and field studies.…”
Section: Other Fracturing Treatmentssupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the complicated flow regime usually occurring after hydraulically fracturing wells with deep damage, it is expected that a small positive skin factor is calculated from buildup data. 1,3 What is observed in Table 1 is consistent with previously published modeling and field studies.…”
Section: Other Fracturing Treatmentssupporting
confidence: 92%
“…To understand the process of FracPac, it is important to study its fracturing aspects, reservoir fluid flow aspects, and operational aspects of the process. The fracturing aspects of FracPac have been discussed recently in the literature by Roodhart, et al 1 , and Meese, et al 2 The reservoir engineering aspects of FracPac have been discussed by Hunt and Soliman, 3 Chen and Raghavan, 4 and Mathur, et al 5 In a simulationbased study, Burton, et al 6 presented the effects of formation permeability and fracture conductivity on performance of FracPac.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] To generate sufficient fracture conductivity in high permeability reservoirs, a stimulation method called a tip screenout (TSO) must be utilized. [9][10][11] One inherent problem with the TSO method is that the treatment must be designed for a low fluid efficiency. 12 In other words, all the pad fluid must leakoff into the formation so that the proppant will bridge near the tip of the fracture.…”
Section: Issues Related To Fracturing High Permeability Gas Reservoirsmentioning
confidence: 99%
“…Given that most fracturing fluids are polymer-based gels, large amounts of fracture fluid leakoff can cause severe formation damage around the fracture, as well as damage within the fracture from polymer filter cake. 1,9,10 Several authors have reported that in high permeability reservoirs, viscous gel can leakoff into the formation up to a depth of 6 inches, leaving polymer residue within the formation. 1,12-14 As a result, an "internal" filter cake can be deposited within the pore spaces of the rock and, if not properly broken with additives, can severely plug the formation.…”
Section: Issues Related To Fracturing High Permeability Gas Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation